2019
DOI: 10.1177/0300060519884151
|View full text |Cite
|
Sign up to set email alerts
|

Association of infections with multiple sclerosis in Gulf Cooperation Council countries: a review

Abstract: Multiple sclerosis (MS) is an autoimmune disease that affects the central nervous system, causing inflammation, demyelination, and neurodegeneration. Infection can play a role in its etiology. Herein, a review is presented of studies that have reported an association between infection and MS risk in countries of the Arabian Gulf region. Searches of the PubMed, Google Scholar, and Science Direct databases were carried out using various search terms, and relevant studies published through January 2019 on the epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 75 publications
(102 reference statements)
0
1
0
Order By: Relevance
“…1 MS has a multifactorial etiology and is triggered by environmental factors in individuals with complex www.nsj.org.sa genetic profiles. [2][3][4][5][6] Obese individuals may have a higher risk of developing MS. A previous study showed that individuals with a body mass index )BMI( of more than 27 kg/m 2 at age 20 years had twice the risk of developing MS than normal-weight individuals. 7 Another study conducted in Norway involving individuals aged 5, 10, 15, 20, 25, and 30 years found that large body sizes )Stunkard's standard body silhouettes 6-9( were associated with an increased risk of MS compared to silhouette 3, particularly at age 25 among female participants.…”
mentioning
confidence: 99%
“…1 MS has a multifactorial etiology and is triggered by environmental factors in individuals with complex www.nsj.org.sa genetic profiles. [2][3][4][5][6] Obese individuals may have a higher risk of developing MS. A previous study showed that individuals with a body mass index )BMI( of more than 27 kg/m 2 at age 20 years had twice the risk of developing MS than normal-weight individuals. 7 Another study conducted in Norway involving individuals aged 5, 10, 15, 20, 25, and 30 years found that large body sizes )Stunkard's standard body silhouettes 6-9( were associated with an increased risk of MS compared to silhouette 3, particularly at age 25 among female participants.…”
mentioning
confidence: 99%